Sikepo: Santri Empowerment In Managing Pondok Pesantren Financial To Make Transparency And Accountability - Lailatul Nurus Shofiyyah; Janah Setiya Nurul Arifa; Ahmad Rokhi Regar; Muhammad Shohibur Rida’; Ahmad Zuhdi Alwan (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) IAIN Pekalongan, 2018)
Islamic Boarding School or generally called Pondok Pesantren (Ponpes) is a community-based educational institution of Islamic religious education that organizes an integrated religious education with other types of education. Ponpes must be able to compete with other general educational institutions by conducting a management. In 2018, Indonesian government issued the accounting guidelines of Ponpes which mainly aimed at empowering economic of Ponpes in order to be able to prepare financial statements. The public volunteers of Economics Faculty of UNNES conducted services at Ponpes Aswaja (Semarang) which had not yet had good financial management. The recording of financial data such as santri’s tuition fee was still manual and the payment recapitulation still used folio books untidily. Consequently, it is difficult to find if the recapitulation is required for accountability. Therefore, it is necessary an integrated financial management system of Ponpes in order to record the financial data properly. The system can also facilitate Ponpes to carry out financial transparency and accountability in accordance with financial accounting standards. The voluntary activities focused on the understanding of Aswaja Ponpes administrators regarding accounting and financial management based on information technology called Sistem Manajemen Keuangan Pondok (Sikepo). The activities were implemented by training and mentoring of administrators based on Participatory Rural Appraisal (PRA). Ponpes administrators were enthusiastic about Sikepo training. Sikepo could improve the understanding of accounting and financial management of Ponpes administrators. Furthermore, the system was then used to record every financial transaction in Ponpes. The final of financial statements were the recapitulation of student tuition fee, the use of funds for daily needs, and other activity reports. This system can also be used in all Ponpes over Indonesia.